1991
DOI: 10.1103/physreva.44.1848
|View full text |Cite
|
Sign up to set email alerts
|

High-resolutionK-shell photoabsorption measurements of simple molecules

Abstract: C2D6 measured with unprecedent energy resolution and signal-to-noise ratio are presented. These spectra reveal many new features in core-excited valence and Rydberg states. Detailed vibrational structures are observed in these spectra, providing valuable information on the geometrical and vibrational properties of the core-excited molecules. In addition, C 1s and N 1s core-hole lifetimes are found to be -120 and -135 meV in these molecules with little dependence on their bonding environments. These results and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
201
2

Year Published

1997
1997
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 287 publications
(215 citation statements)
references
References 26 publications
12
201
2
Order By: Relevance
“…Calibration: -7.64 eV relative to the center of the overlapping C 1s f 3s(ν)0) and the C 1s f 3s(ν)1) transitions in CO2 (292.8 eV). 11 The spectrum of poly(ethylene oxide) is quite simple, representing the contribution from the single CH 2 carbon atomic environment in the polymer, with a strong transition at 289 eV and a weaker but clearly resolved feature at 289.7 eV. In the C 1s NEXAFS spectrum of poly(ethylene oxide) published by Kikuma and Tonner 27 only one feature is observed at ∼289 eV, but this difference is simply a function of the improved spectral resolution in the present work.…”
Section: Distinguishing Urea and Carbamatementioning
confidence: 99%
See 1 more Smart Citation
“…Calibration: -7.64 eV relative to the center of the overlapping C 1s f 3s(ν)0) and the C 1s f 3s(ν)1) transitions in CO2 (292.8 eV). 11 The spectrum of poly(ethylene oxide) is quite simple, representing the contribution from the single CH 2 carbon atomic environment in the polymer, with a strong transition at 289 eV and a weaker but clearly resolved feature at 289.7 eV. In the C 1s NEXAFS spectrum of poly(ethylene oxide) published by Kikuma and Tonner 27 only one feature is observed at ∼289 eV, but this difference is simply a function of the improved spectral resolution in the present work.…”
Section: Distinguishing Urea and Carbamatementioning
confidence: 99%
“…For energy scale calibration, CO 2 gas was added to the He purge in the microscope and the transmission spectrum of the mixture of the polymer and CO 2 gas was recorded. The energies of the CO 2 f Rydberg transitions from the high-resolution NEXAFS spectra of Ma et al 11 were used to calibrate these spectra. These values are consistent with the calibrated electron energy loss spectra of Tronc et al 12 The calibration is documented in the tables of spectral assignments.…”
Section: Introductionmentioning
confidence: 99%
“…The work of Adachi et al [16] further demonstrates that no Renner-Teller effect is present in any of the 1s → Rydberg excited states, which suggests that the axial-recoil approximation is fully valid in these cases and allows reliable symmetry information from ARIY measurements in the corresponding spectral regions to be obtained. Based on the symmetry information available from their data, in combination with ab initio calculations and spectral features readily observed by Ma et al [15], several new assignments were made by Adachi et al [16].…”
Section: Introductionmentioning
confidence: 99%
“…At about the same time, the first nitrogen K-shell photoabsorption spectrum of N 2 O was recorded at Stanford [14], which agreed well with the EELS measurements and confirmed the assignments made based on the ECM. In the early 1990s Ma et al [15] succeeded in recording a substantially improved, high-resolution photoabsorption spectrum of N 2 O at the nitrogen K edges, which revealed many more electronic states than seen before and readily suggested that vibrational fine structures were present, but their assignments were only tentative.…”
Section: Introductionmentioning
confidence: 99%
“…Samples were deposited on silicon nitride membranes and the microscope was used to find a small particle with peak optical density (OD) below 2 OD units, so that the spectra would not be distorted by absorption saturation. The energy scale was calibrated using the sharp Rydberg transitions of CO 2 [31]. Transmission spectra through the particle were converted to absorption spectra using the Io spectrum recorded off the particle.…”
Section: Solid State Measurements By Stxmmentioning
confidence: 99%